New pixel circuits for controlling threshold voltage by back‐gate bias voltage using crystalline oxide semiconductor FETs. Issue 1 (28th December 2015) - Kaneyasu, Makoto; Toyotaka, Kouhei; Shishido, Hideaki; Isa, Toshiyuki; Eguchi, Shingo; Miyake, Hiroyuki; Hirakata, Yoshiharu; Yamazaki, Shunpei; Dobashi, Masayoshi; Fujiwara, Chieko
Abstract: We devised a threshold voltage compensation pixel circuit using back‐gate bias voltage. Variation in threshold voltages can be reduced to 10% in simulation while improving the saturation characteristics of a driving transistor. The pixel circuit can compensate not only threshold variation but also mobility variation. We fabricated a 5.29‐in Quad‐VGA organic light emitting diode display using this pixel circuit. Abstract : We devised a threshold voltage compensation pixel circuit using back‐gate bias voltage. Variation in threshold voltages can be reduced to 10% in simulation while improving the saturation characteristics of a driving transistor. The pixel circuit can compensate not only threshold variation but also mobility variation. We fabricated a 5.29‐in Quad‐VGA organic light emitting diode display using this pixel circuit.